Complete mitochondrial genome of the MacClelland’s Coral Snake Sinomicrurus macclellandi (Reinhardt, 1844) (Serpentes: Elapidae) - Li-Zhong Yao; Yan-An Gong; Xin-Sheng Tang (Mitochondrial DNA. Part B. Resources, 2020)
We report the complete mitochondrial genome (mitogenome) sequence of the MacClelland’s Coral Snake Sinomicrurus macclellandi (Reinhardt, 1844). The sequence was determined by shotgun sequencing. The mitogenome of S. macclellandi is 17,120 bp in length and contains 13 protein-coding genes (PCGs), 22 tRNA genes, two ribosome RNA genes, and two noncoding regions. Most genes of S. macclellandi were distributed on the H-strand, except for the ND6 subunit gene and eight tRNA genes which were encoded on the L-strand. The phylogenetic tree of S. macclellandi and 12 other related species was built. The DNA data presented here will be useful to study the evolutionary relationships and genetic diversity of S. macclellandi.